2017
DOI: 10.1097/hjh.0000000000001332
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of essential hypertension in the population of Tatars from Russia

Abstract: Our results suggest that rs5351 single-nucleotide polymorphism is a strong independent predictor of essential hypertension in men of Tatar ethnic origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In Korean population, VEGF-2578C>A and -1154G>A polymorphisms have a protective effect on hypertension susceptibility [22]. VEGFA 2549 (18) I/D and VCAM1 rs3917010 were associated with SBP and DBP in Russian Tatars [23]. Observational data from a large number of participants showed that VEGF-1154G/A polymorphism can prevent hypertension [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…In Korean population, VEGF-2578C>A and -1154G>A polymorphisms have a protective effect on hypertension susceptibility [22]. VEGFA 2549 (18) I/D and VCAM1 rs3917010 were associated with SBP and DBP in Russian Tatars [23]. Observational data from a large number of participants showed that VEGF-1154G/A polymorphism can prevent hypertension [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…As a major risk factor for cardiovascular and cerebrovascular diseases, essential hypertension (EH) is the top cause of death worldwide. 1,2 EH is commonly described as a complex disease indicated by a chronic elevation of blood pressure (BP) with no clear cause. It is a classic example of a multifactorial trait caused by the inheritance of susceptibility genes and multiple environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…It is a classic example of a multifactorial trait caused by the inheritance of susceptibility genes and multiple environmental factors. 1,3 Efforts to identify the genes responsible for the occurrence and development of EH are useful for understanding the genetic and pathogenic mechanisms behind it. However, genetic contributions are difficult to elucidate for EH.…”
Section: Introductionmentioning
confidence: 99%